Can Student Loans Improve Accessibility to Higher Education and Student Performance? An Impact Study of the Case of SOFES, Mexico - Canton, Erik; Blom, Andreas (World Bank, Washington, D.C., 2013)
Financial aid to students in tertiary education can contribute to human capital accumulation through two channels: increased enrollment and improved student performance. We analyze the quantitative importance of both channels in the context of a student loan program (SOFES) implemented at private universities in Mexico. With regard to the first channel, enrollment, results from the Mexican household survey indicate that financial support has a strong positive effect on university enrollment. Given completion of upper secondary education, the probability of entering higher education rises 24 percent. Two data sources are used to investigate the second channel, student performance. Administrative data provided by SOFES are analyzed using a regression-discontinuity design, and survey data enable us to perform a similar analysis using a different control group. Empirical results suggest that SOFES recipients show better academic performance than students without a credit from SOFES. However, the results cannot be interpreted as a purely causal impact of the student loan program, since the impacts also could reflect (self-) selection of students.